Modernizing the Algerian tax system as a way to activate and develop the tax system - سعيدي شهرة; قمان عمر (Finance and Business Economies Review, 2020)
In light of the rapid changes taking place in the world, and technological and economic developmentswhich Algeria was not immune from, the General Directorate of Taxes has initiated several reforms in linewith these transformations, this study addresses these reforms and aims to highlight the most important axesof modernizing tax administration. It was concluded that the General Directorate of Taxes had undertaken several reforms in the legislativeside as well as the structural side that had a positive impact on the cost-effectiveness and effectiveness of theAlgerian tax system, but it is not sufficient, it must be accompanied by special reforms at the level of thebanking system and the Algerian stock exchange and several laws that are fully related to the tax system.